Re‐opening the window on fenestration as a treatment for acute thoracolumbar intervertebral disc herniation in dogs. (April 2017) - Freeman, P.; Jeffery, N. D.
Abstract : Acute thoracolumbar intervertebral disc herniation in dogs is a common cause of "back" pain, pelvic limb paresis or paralysis and incontinence. Treatment of this condition has long been a source of controversy, especially since the introduction of surgical interventions in the 1950s. Unfortunately, formal clinical trials to compare efficacy of conservative and surgical interventions have never been carried out and the current lack of clinical equipoise on this subject now precludes such a trial on ethical grounds. In this article we re‐examine and discuss earlier published data on recovery associated with the various therapies, focusing on evidence suggesting that decompressive surgery and fenestration may be equally efficacious.